Model-Driven Adaptation of Ubiquitous Applications - Parra, Carlos; Duchien, Laurence (Electronic Communications of the EASST, 2008)
In ubiquitous computing, applications are executed in powerful and mobile devices allowing users to enter and leave frequently from diverse locations. Mobility becomes the rule rather than the exception. Software should be able to change its behavior and react to changes on its environment. In this proposal paper we discuss several challenges for context-aware software development and present our proposal to achieve software adaptation based on context information. We use a model of context as a starting point for a process where components are generated, deployed, and loaded on mobile devices.